2022
DOI: 10.1039/d2ta05858h
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic polyurea network with exceptional creep resistance

Abstract: Thermosetting polymers enjoy outstanding static performance at the expense of poor reprocessability and recyclability. The design of covalent adaptable networks (CANs) provides a possible solution, but most of them show...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Many researchers have incorporated covalent adaptable networks (CANs) in synthesizing recyclable epoxy resins, including imine exchange, , transesterification, disulfide exchange, boronic ester exchange, , siloxane exchange, and DA/retro-DA reaction . However, due to the introduction of CANs, the dynamic networks were susceptible to creep when used in engineering and structural fields, and creeping of these materials usually occurred around the topology freezing temperature ( T v ), which was usually much lower than the T g . Many efforts have been made to improve the creep resistance, such as through controlling the availability of cross-linking or incorporation of permanent cross-linking. For example, Xu et al prepared a type of dihydrazone-based dynamic covalent epoxy network containing dihydrazone with an initial creep temperature of about 105 °C . Previously, we have reported that the initial creep temperature of a recyclable epoxy resin increased about 20 °C with ferulic acid-based hyperbranched epoxy resin (FEHBP) .…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have incorporated covalent adaptable networks (CANs) in synthesizing recyclable epoxy resins, including imine exchange, , transesterification, disulfide exchange, boronic ester exchange, , siloxane exchange, and DA/retro-DA reaction . However, due to the introduction of CANs, the dynamic networks were susceptible to creep when used in engineering and structural fields, and creeping of these materials usually occurred around the topology freezing temperature ( T v ), which was usually much lower than the T g . Many efforts have been made to improve the creep resistance, such as through controlling the availability of cross-linking or incorporation of permanent cross-linking. For example, Xu et al prepared a type of dihydrazone-based dynamic covalent epoxy network containing dihydrazone with an initial creep temperature of about 105 °C . Previously, we have reported that the initial creep temperature of a recyclable epoxy resin increased about 20 °C with ferulic acid-based hyperbranched epoxy resin (FEHBP) .…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon has also been observed in other hydrogen-bond cross-linked polymer materials. 3,4,9 It is noteworthy that although the processing temperature of PETMP-acac TbOTf 3 4:1 is higher than that of PETMP-acac Tb(NO 3 ) 3 4:1, its creep strain is significantly higher (over 110%) at the same creep conditions (Figures 3B and S24− S25). Moreover, PETMP-acac TbOTf 3 4:1 shows a faster stress-relaxation behavior with the relaxation time less than 200 s at 80 °C (Figure S26).…”
Section: Mechanism Studymentioning
confidence: 94%
“…The derived thermoset polymers, known as vitrimers or covalent adaptable networks (CANs), can be reprocessed like thermoplastics due to the bond exchange process, while maintaining a high mechanical strength and dimensional stability. To date, a variety of dynamic covalent chemistries have been implemented into thermosets, such as transesterification, Diels–Alder chemistry, disulfide exchange, boronic ester transesterification, imine exchange, and so on. However, most of the CANs reported so far have a trade-off between the mechanical strength and reversible properties. More importantly, the bond exchange process renders poor creep resistance when the materials are imposed with a constant force (especially at higher temperatures), leading to severe deformation during service.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, 0BT3PMDA showed the lowest creep resistance, and its strain quickly increased to above 30% in just 10 s. Besides, the strain recovered obviously aer withdrawing the stress due to the disorientation of the molecular chains, which was negligible for the 0.8BT3PMDA vitrimer because the orientation of its molecular chains was suppressed by its crosslinking networks; meanwhile, the stress could be relaxed by exchange reactions. In contrast, due to its high gel content and slow exchange reaction rate, 0.8BT6ADR exhibited the highest creep resistance and maintained nearly constant strain even aer 1000 s. 55 Although 0.8BT3PMDA had a much higher gel content, 0BT6ADR obviously possessed a higher creep resistance because the former has a lower melt strength due to the fast exchange reaction, creating viscous-ow behavior. With a decrease in temperature, the exchange reaction rate became slower.…”
Section: Construction Of Covalent Adaptable Networkmentioning
confidence: 95%